THE ROLE OF THE STORY GENRE IN DEVELOPING THE SPEECH COMPETENCE OF PRIMARY SCHOOL STUDENTS (Scientific journal of the Fergana State University, 2026)
Modern education aims to ensure the comprehensive development of the student's personality, including the acquisition of advanced speech skills. In all cases, and especially within the educational process, speech plays a central role, and developing students' communication abilities becomes an essential component of educational practice. This article explores the importance of the narrative genre in enhancing the speech competence of primary school students and discusses the life skills to be developed through speech development in the learning process.